Role of Virudhahara in Current Lifestyle Diseases (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda has long emphasized the importance of a healthy lifestyle and proper dietary habits to prevent illness. Ayurveda places great importance on a balanced diet as a fundamental pillar of overall health and well-being. A significant concept within Ayurveda is Viruddha Ahara, which refers to the consumption of incompatible or unwholesome dietary habits. The Consumption of Viruddha ahara increased in present era due to modern food habits. Individuals who adopt such food habits are more susceptible to various health conditions. The rise in lifestyle diseases, such as type 2 diabetes, hypertension, obesity, heart disease, dyslipidaemia, and infertility, particularly in urban areas, is largely attributed to incompatible eating practices. As these conditions are closely linked to diet and lifestyle, the concept of Viruddha Ahara becomes increasingly relevant. This article explores the relationship between Viruddha Ahara and the growing prevalence of lifestyle-related diseases. A comprehensive review of modern medical and Ayurvedic literature was conducted through freely accessible platforms like PubMed and Google Scholar. The review of available data indicates that Viruddha Ahara contributes significantly to the onset of various health conditions. Therefore, it is essential to raise awareness about the harmful effects of consuming incompatible foods and encourage healthier eating practices.